Komunikasi Krisis dalam Isu Kebangsaan: Studi Kasus Peran Pemerintah dalam Menjaga Pancasila - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Atikah Firdaus; Zaky Amrullah Zain; Robith Taufiqurrahman; Aulia Ashari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to analyze the crisis communication strategy implemented by the government to address national issues that could put the ideology of Pancasila at risk. Using a case study approach, this study examines how the government managed communication during the crisis, including identifying key stakeholders, transferring messages, and using communication channels. This data was collected by analyzing political documents and media reports also library research. The results show that the effectiveness of government crisis communication is greatly influenced by the speed of response, transparency of information, and the ability to build an integrated dialog with different groups of people. In addition, this research also shows the importance of positive and continuous communication to incorporate state resistance to ideological threats. The effectiveness of this research provides the government and other interest groups with valuable findings in the development of effective communication strategies to maintain and strengthen the value of Pancasila on the issue of time challenges.